REVISION MASTOIDECTOMY AND OTO-ENDOSCOPY - Salahuddin Ayubi; Sohail Ahmad; Ashif Ali (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To evaluate the reasons for persistent discharging mastoid cavities, the operative findings during revision surgery and medium term outcome. MATERIALS AND METHODS: Thirty four patients who had persistently discharging mastoid cavities underwent revision mastoidectomies between Jan 2008 to July 2013 were analyzed retrospectively. RESULTS: Recurrent or residual cholesteatoma was found in 86.6% of our cases. Poorly shaped cavities, high facial ridge, meatal stenosis/ inadequate concho-meatoplasty were the main reasons of failure of primary surgery. Peri-sinus and mastoid tip cells were the most frequent sites of residual air cells. A residual air bone gap ABG of < = 30dB was achieved in 60% of our cases. CONCLUSION: The characteristics and surgical outcome of persistently discharging mastoid cavities must be fully understood for complete control of disease and use of otoendoscope could decrease the recurrence rate.